The impact of brand reputation on financial performance - Tavares, Tomás de Barros e Carvalhosa (2023)
As the business world moves towards the digital era, conversations about brands are being held around the world, which can affect the perception that people have about companies. Consequently, it has become imperative to address the topic of brand reputation management so that companies have control over the information being shared about them to protect, preserve and enhance their brands and businesses. Following this reasoning, this thesis investigated the impact of brand reputation in the financial performance of companies in Portugal, particularly, in the banking sector. It analysed how brand reputation performs as a differentiating factor for businesses and may represent a source of competitive advantage that allows companies to outperform their competitors and survive. Qualitative and quantitative data were gathered through experts’ interviews and surveys to consumers, investors, journalists and C-level/board directors. The aim of this exercise was to analyse how people develop perceptions of brands and how different brand attributes affect the reputation of a brand reputation and financial performance of companies across different sectors of the Portuguese economy. Furthermore, this dissertation compared the performance of strongly perceived brands with its competitors and investigated how a reputational crisis affects the financial performance of companies through the analysis of Banco Espírito Santo’s governance scandal case study.